Variability and multiplicity in the meanings of stereotypical gendered speech in Japanese. (16th November 2015) - Okamoto, Shigeko
Abstract : Recent research on the use of gendered speech in Japanese has demonstrated extensive within-gender diversity, suggesting that the relationship between linguistic forms and gender is variable, not fixed. While this diversity in use suggests a diversity in interpretation, the latter has not been adequately examined in its own right and deserves closer attention, given that it has important implications for the relationship between linguistic forms and social meanings. To address this gap, this study analyses both native speakers' metapragmatic comments on the use of gendered linguistic forms and the interpretation of such forms used in situated conversations. It considers how and why forms normatively interpreted as feminine or masculine may be (re)interpreted differently by different persons or in different social contexts. Drawing on the notion of indirect and variable indexicality, I consider how such diverse and multiple interpretations can be accounted for in a theoretically coherent manner.